The Engagement In Qur’anic Sciences: A Correlation Between al-Manṭūq wa al-Mafhūm and Gracia’s Hermeneutics - Achmad Khusnul Khitam (Studia Quranika, 2024)
This article aims to observe the substantive contact between the concept of al-manṭūq wa al-mafhūm in uṣūl al-fiqh and the three functions of Gracia’s hermeneutics. This article focuses on elaborating both conceptions substantively and applying them to some verses of the Qur’an to understand the rendezvous of both concepts, particularly in the interpretative sphere. This article uses both semantic and interpretative approaches in order to analyze the objects. Based on this result, it is found that there is a substantive contact between both conceptions. Firstly, both conceptions are used to determine the original meaning of the text; the uṣūl al-fiqh employs the term of al-ma'nā al-manṭūq, while Gracia’s hermeneutics uses the “historical function.” Secondly, both conceptions can also be used to produce new contemporary meanings; the uṣūl al-fiqh utilizes the term of al-ma'nā al-mafhūm, while Gracia’s hermeneutics employs the “meaning function.” Third, a certain response must be made to the contemporary meaning. In this regard, the uṣūl al-fiqh stipulates this in the process of istinbāṭ al-ḥukm, while Gracia’s hermeneutics calls this as the “implicative function.”